Emerging Roles of lncRNA MSC-AS1 in Cancer: Molecular Mechanisms, Clinical Implications, and Therapeutic Potential - Mir, Mohsen; Kurbanbayeva, Asel; Ruzieva, Mukhayya; Yaxshimuratov, Murodjon; Mirzayev, Otabek; Khadieva, Dora; Ebrahimzade, Mohammadreza; Hamzeh, Soroosh (Asian Pacific Journal of Cancer Biology, 2025)
Overview: Long non-coding RNAs (lncRNAs) are key regulators of tumor biology, affecting proliferation, apoptosis, metastasis, and treatment resistance. Among them, Musculin Antisense RNA 1 (MSC-AS1) has attracted increasing attention for its oncogenic roles across multiple cancers. This review summarizes current knowledge on MSC-AS1, emphasizing molecular mechanisms, clinical relevance, and therapeutic potential. Methods: A comprehensive literature search of PubMed, Scopus, and Web of Science identified studies published 2015–2024 that investigated MSC-AS1 in cancer. Eligible articles examined its functional roles, implicated signaling pathways, regulatory interactions (e.g., lncRNA–miRNA–mRNA axes), and diagnostic, prognostic, or therapeutic implications. Results: Evidence consistently shows that MSC-AS1 is frequently upregulated in gastric, hepatic, pancreatic, and colorectal cancers. Mechanistically, MSC-AS1 contributes to tumor progression mainly through lncRNA–miRNA–mRNA regulatory networks, promoting malignant phenotypes and therapeutic resistance. Clinically, elevated MSC-AS1 expression correlates with poor prognosis, supporting its utility as a biomarker for diagnosis and prognosis and as a candidate target for precision oncology. Conclusion: MSC-AS1 functions as an oncogenic lncRNA across multiple gastrointestinal and hepatobiliary malignancies, driving disease through competitive regulatory networks and associating with adverse outcomes and resistance. Current evidence positions MSC-AS1 as a promising biomarker and a potential therapeutic target; future work should validate its clinical performance and evaluate targeted interventions against MSC-AS1-mediated pathways.